Magnetic Resonance Imaging Versus Computed Tomography Angiography Based Selection for Endovascular Therapy in Patients With Acute Ischemic Stroke. Issue 2 (February 2019) - Kim, Joon-Tae; Cho, Bang-Hoon; Choi, Kang-Ho; Park, Man-Seok; Kim, Beom Joon; Park, Jong-Moo; Kang, Kyusik; Lee, Soo Joo; Kim, Jae Guk; Cha, Jae-Kwan; Kim, Dae-Hyun; Nah, Hyun-Wook; et al.
Abstract : Background and Purpose—: Randomized trials comparing the use of multimodal magnetic resonance imaging (MRI) to multimodal computed tomography (CT)/ CT angiography (CTA) for selecting candidates for endovascular therapy (EVT) have not been reported. This study aimed to elucidate whether MRI-based selection for EVT is safe and effective within and after a 6-hour time window compared with conventional CTA-based selection. Methods—: Data from a prospective, nationwide, multicenter stroke registry were analyzed. Workflow timelines were compared between patients selected for EVT based on MRI (the MRI group) and CTA (the CTA group). Multivariable ordinal and binary logistic regression analyses were performed to explore the relationships between decision imaging for EVT and clinical outcomes, including good and excellent outcomes (modified Rankin Scale scores of 0–2 and 0–1, respectively) at 3-month, modified Rankin Scale score distributions and safety outcomes (symptomatic intracranial hemorrhage [SICH] and mortality). Results—: Ultimately, 1265 patients (age, 69±12 yrs; men, 55%) were enrolled in this study. The median National Institutes of Health Stroke Scale score was 15 (11–19). All workflow time metrics were significantly delayed in the MRI group compared with the CTA group. There was no difference in good 3-month outcomes in patients arriving within 6 hours of onset between the MRI and CTA groups (38.1% versus 38.5%), but SICH and mortality rates were lower in the MRI group than the CTA group (3.8% versus 7.7%, P =0.01 for SICH; 15.4% versus 20.9%, P =0.04 for mortality). In the multivariable analysis, decision imaging was not significantly associated with 3-month functional outcomes (all P >0.1) or mortality ( P =0.051); however, the MRI group was less likely to develop SICH than the CTA group ( P =0.01; odds ratio, 0.34 [95% CI, 0.17–0.77]). Conclusions—: Our study found MRI-based selection for EVT was not associated with improving functional outcome compared with CT-based selection, but may be better at reducing the risk of SICH, despite the delays in all workflow time metrics. Abstract : Supplemental Digital Content is available in the text.